Nanoarchitectonics for supercapacitor: biomass vs. fullerene - Shrestha, Lok Kumar; Ariga, Katsuhiko (Frontiers in Batteries and Electrochemistry, 2024)
The recognition of the importance of nanostructures is mainly due to the development of nanotechnology. For further developments in materials sciences, a concept that integrates nanotechnology with material chemistry to fabricate functional materials has to be proposed. Nanoarchitectonics will carry out this task. In nanoarchitectonics, we architect functional material systems from nano-units (atoms, molecules, nanomaterials). The methodology is not specific to any particular material or application. It covers a wide range. Therefore, nanoarchitectonics can be thought of as the method for everything in materials science. As typical demonstrations for usages of nanoarchitectonics, this review paper presents our work on nanoarchitectonics for supercapacitors. We divide it into two categories with different approaches. The first is the development of carbon materials as supercapacitor electrode materials from biomass. The second category is preparing carbon materials using structures created by supramolecular assembly of fullerenes such as C60 and C70. By presenting examples using opposite starting materials, a complex natural material, and an ultimately simple molecule, we will demonstrate the versatility and breadth of possibilities of this approach.